2021
DOI: 10.3390/healthcare9040419
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Cognitive Walking Program on Improving Cognitive Function and Physical Fitness in Older Adults

Abstract: Exercise and cognitive training can improve the brain-related health of the elderly. We investigated the effects of a cognitive walking program (CWP) involving simultaneous performance of indoor walking and cognitive training on cognitive function and physical fitness compared to normal walking (NW) outdoors. Participants were grouped according to whether they performed regular exercise for at least 3 months prior to the participation in this study. Active participants were assigned to the CWP-active group (CW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Ageism is an age-based stereotype, prejudice, and discrimination against the elderly, and previous studies have shown a strong association between ageism and the physical and psychological health risks of the elderly [ 19 , 20 , 21 ]. The speed of aging varies greatly among individuals, and the differences between individuals tend to increase with age [ 22 , 23 ]. In addition, physical, mental, and social consequences of aging vary from person to person [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ageism is an age-based stereotype, prejudice, and discrimination against the elderly, and previous studies have shown a strong association between ageism and the physical and psychological health risks of the elderly [ 19 , 20 , 21 ]. The speed of aging varies greatly among individuals, and the differences between individuals tend to increase with age [ 22 , 23 ]. In addition, physical, mental, and social consequences of aging vary from person to person [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though not beneficial for improving motor function of the brain, the CWP has been shown to improve cognitive function in healthy older adults. Kang et al (2021) investigated the effects of the CWP on cognitive function in both active and sedentary older adults using the same exercise protocol (60 min per session, 3 times a week, for 6 months; cognitive function measured at baseline, 3 months, and 6 months after program onset). Cognitive function was evaluated using the Seoul Neuropsychological Screening Battery (SNSB-II) ( Lee et al, 2018 ) by certified clinical psychologists who had at least 3 years of experience with administering the SNSB-II.…”
Section: Discussionmentioning
confidence: 99%
“…It is also related to improved cognitive and executive function ( Prohaska et al, 2009 ; Weuve et al, 2004 ; Yogev-Seligmann et al, 2008 ). Given that, Kang et al (2021) recently developed an exercise program called the cognitive walking program (CWP), which was designed to improve cognitive function of the elderly by stimulating their memory, attention, visual perception and walking ability while performing various stepping patterns that require specific motions of the upper and lower extremities. The effect of the CWP on improving cognitive function in healthy older adults has been demonstrated in a recent study by Kang et al (2021) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise and cognitive training can improve brain-related health in older adults [ 19 ]. Tai chi is a Chinese intangible cultural heritage that improves physical and mental health and is as easy to learn, safe, convenient, and popular as walking.…”
Section: Introductionmentioning
confidence: 99%